Tracking microbial interactions with NanoSIMS. (October 2016) - Musat, Niculina; Musat, Florin; Weber, Peter Kilian; Pett-Ridge, Jennifer
Graphical abstract: Highlights: NanoSIMS-FISH correlates phylogeny and tracer assimilation by single cells. NanoSIP can map many elements in parallel, most often C, N, O, P and S. NanoSIP can help resolve trophic interactions in microbial communities. Some sample treatments modify the elemental/isotopic composition of cells. Complementary methods assist nanoSIP to better understand microbe interactions. Abstract : The combination of stable isotope probing (SIP), NanoSIMS imaging and microbe identification via fluorescence in situ hybridization (FISH) is often used to link identity to function at the cellular level in microbial communities. Many opportunities remain for nanoSIP to identify metabolic interactions and nutrient fluxes within syntrophic associations and obligate symbioses where exchanges can be extremely rapid. However, additional data, such as genomic potential, gene expression or other imaging modalities are often critical to deciphering the mechanisms underlying specific interactions, and researchers must keep sample preparation artefacts in mind. Here we focus on recent applications of nanoSIP, particularly where used to track exchanges of isotopically labelled molecules between organisms. We highlight metabolic interactions within syntrophic consortia, carbon/nitrogen fluxes between phototrophs and their heterotrophic partners, and symbiont–host nutrient sharing.